Role for Endovascular Therapy in Chronic Mesenteric Ischemia - Romaric Loffroy (Canadian Journal of Gastroenterology, 2009)
Chronic mesenteric ischemia is a rare condition that is caused by stenosis or occlusion of the mesenteric arteries and usually manifests as abdominal pain. While surgical revascularization has been the standard treatment for symptomatic patients, recent advances in interventional devices and techniques have made endovascular treatment feasible and effective. Percutaneous transluminal angioplasty with stent placement is now recognized as a minimally invasive means of obtaining good long-term results with an acceptable recurrence rate; consequently, the technique is suggested for the primary treatment of chronic mesenteric ischemia. The present article discusses the indications and principles of endovascular treatment, and reviews the literature, with emphasis on short- and long-term outcomes, particularly morbidity and mortality rates.